PENGAPLIKASIAN PENAWARAN PADA SISTEM PENJUALAN UNTUK GLOVELLA SHOP BERBASIS E-COMMERCE (Information Technology and Telematics, 2013)
Business competitors engaged in fashion and accessories is now getting tougher, as the development of technology so fast it takes application that is able to help purchase online. With the application and sale of fashion accessories online, customers need not come to the store and to expand marketing network and kustomersnya. Simply by accessing the web and transfer the amount of money the clothes or accessories that are needed to be sent to the destination. The system is made ​​with a prototype method that is not directly conditioned on the actual circumstances. Developing applications using the Personal Home Page tools (PHP) as pemogramannya language and MySQL as the database. In making the various tools used pembatu development application used like Adobe Dreamweaver and Adobe Photoshop CS3. With this system it is able to provide layananan purchase clothes and accessories online bargain Keywords: E-Commerse, Glovella Shop, Special Applications.